Embodied Consciousness: A Philosophical Inquiry into the Panch Kosh Framework of the Taittiriya Upanishad (Journal of Informatics Education and Research, 2025)
This paper presents a philosophical inquiry into the Panch Kosh (five sheaths) framework as elucidated in the Taittiriya Upanishad, offering a nuanced exploration of the Vedantic view of embodied consciousness. The Panch Kosh theory—comprising Annamaya (physical), Pranamaya (vital), Manomaya (mental), Vijnanamaya (intellectual), and Anandamaya (bliss)—serves as a profound ontological model that illustrates the multilayered nature of the self. Through a close textual analysis and comparative philosophical approach, this paper investigates the metaphysical underpinnings and the teleological progression embedded within the sheaths. Furthermore, it examines the implications of this model in understanding consciousness, self-realization (Atma Jnana), and the journey from the gross to the subtle. By engaging with both classical commentaries and contemporary philosophical discourse, the study positions the Panch Kosh framework as a vital contribution to global conversations on mind-body dualism, integral psychology, and spiritual anthropology.